2014
DOI: 10.1016/j.ydbio.2014.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Sfrp1a and Sfrp5 function as positive regulators of Wnt and BMP signaling during early retinal development

Abstract: Axial patterning of the developing eye is critically important for proper axonal pathfinding as well as for key morphogenetic events, such as closure of the optic fissure. The dorsal retina is initially specified by the actions of Bone Morphogenetic Protein (BMP) signaling, with such identity subsequently maintained by the Wnt-β catenin pathway. Using zebrafish as a model system, we demonstrate that Secreted frizzled-related protein 1a (Sfrp1a) and Sfrp5 work cooperatively to pattern the retina along the dorso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 45 publications
0
20
0
Order By: Relevance
“…A recent study has, however, reported increased expression of BMPs after inhibition of BMP signaling in zebrafish retinal development (Holly et al, 2014), without discussing a possible negative feedback mechanism. Neither did the authors examine whether retinal exposure to BMPs caused a decrease in BMP expression in the developing zebrafish retinas, which otherwise would have represented a second case of negative BMP auto-regulation.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has, however, reported increased expression of BMPs after inhibition of BMP signaling in zebrafish retinal development (Holly et al, 2014), without discussing a possible negative feedback mechanism. Neither did the authors examine whether retinal exposure to BMPs caused a decrease in BMP expression in the developing zebrafish retinas, which otherwise would have represented a second case of negative BMP auto-regulation.…”
Section: Discussionmentioning
confidence: 99%
“…The over-activation of Notch results in a pulse of proliferation followed by a compensatory downregulation of ligand, and eventually, differentiation, creating a bias toward early born neurons. Sfrps also facilitate interactions between Wnts with BMPs in the process of retinal dorsal-ventral patterning [45]. Sfrps, then, may be critical players in regulating the coordinated activities of multiple signaling pathways during retinogenesis, thereby influencing the context for associated Notch activity.…”
Section: Receptor Cleavage Regulationmentioning
confidence: 99%
“…5) showed a reduced association of Bmp3 with Sfrp5 compared with that of Mest . This observation was somewhat surprising since Sfrp5 has been shown to modulate BMP signaling in the regulation of organogenesis [27] and retinal development [28] in zebrafish. However, although it is well recognized that significant cross-talk occurs between the Wnt and BMP/Smad signaling pathways [29, 30] and BMP and Wnt signaling are important mediators of adipogenesis [31], very little is known in regards to specific Sfrp5 -mediated effects on BMP signaling in mammals.…”
Section: Discussion/conclusionmentioning
confidence: 99%